Sustained censorship in VE (2026-05) (Venezuela) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Venezuela. Data sourced from OONI.
Censorship Incident ID: VE-2026-0408. Severity: critical. Confidence: 77%